2007
DOI: 10.1021/ja0707198
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain ab Initio Study of Charge Relaxation and Recombination in Dye-Sensitized TiO2

Abstract: In order to investigate the electron dynamics at the alizarin/I2-/TiO2 interface this study uses a novel state-of-the-art quantum-classical approach that combines time-dependent density functional theory with surface hopping in the Kohn-Sham basis. Representing the dye-sensitized semiconductor Grätzel cell with the I-/I3- mediator, the system addresses the problems of an organic/inorganic, molecule/bulk interface that are commonly encountered in molecular electronics, photovoltaics, and photoelectrochemistry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
270
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(278 citation statements)
references
References 96 publications
7
270
1
Order By: Relevance
“…The surface hopping method has been implemented within DFT 20,33,34 for calculations of systems on the order of 100 atoms and with durations of up to a few picoseconds. In particular, surface hopping simulations using a time-dependent KS (TDKS) approach 20 have been used to analyze non-adiabatic dynamics in a number of relatively large systems; [42][43][44] this TDKS approach 20 has been compared with the more accurate linear-response time-dependent DFT (LR-TDDFT) method 34 by performing non-adiabatic simulations for different systems. 45 The results show that the simpler and computationally more efficient TDKS approach yields a very reasonable description of the systems analyzed, the agreement with the more accurate method being better for larger systems.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The surface hopping method has been implemented within DFT 20,33,34 for calculations of systems on the order of 100 atoms and with durations of up to a few picoseconds. In particular, surface hopping simulations using a time-dependent KS (TDKS) approach 20 have been used to analyze non-adiabatic dynamics in a number of relatively large systems; [42][43][44] this TDKS approach 20 has been compared with the more accurate linear-response time-dependent DFT (LR-TDDFT) method 34 by performing non-adiabatic simulations for different systems. 45 The results show that the simpler and computationally more efficient TDKS approach yields a very reasonable description of the systems analyzed, the agreement with the more accurate method being better for larger systems.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Ab initio molecular dynamics, which marries concepts of quantum mechanical forces and excitations, presents a more sophisticated approach to study dye···TiO 2 buried interfaces; [39][40][41] these enable both dynamic structural and energetic information. Such studies are generally being reported on a single system at this stage, owing to their signifi cant computational outlay.…”
Section: Further Developments For the Molecular Engineering Of Dsc Dyesmentioning
confidence: 99%
“…On the other hand, it has been shown both theoretically [17,45,54] and experimentally [24,46] that the alizarin excited state is positioned near the TiO 2 conduction band edge. The simulation for the alizarin/TiO 2 coupled system showed that the electron is initially injected into localized surface states and subsequently delocalized on a !…”
Section: Direct Electron Transfer Vs Electron Transfer Through the Sumentioning
confidence: 99%
“…Moreover, the alizarin-sensitized TiO 2 system, where the molecular photoexcited state is at the edge of the conduction band, [17,24,45] represents an interesting case of a dye/semiconductor coupled system. In spite of this, an extremely fast injection for alizarin-sensitized TiO 2 nanoparticles in solutions in the sub-10 femtosecond time scale has been observed in the experiment [13] and was confirmed by theory.…”
Section: Introductionmentioning
confidence: 99%